2006
DOI: 10.1007/s11274-005-9025-0
|View full text |Cite
|
Sign up to set email alerts
|

Laccase activities of a soil fungus Penicillium simplicissimum in relation to lignin degradation

Abstract: The laccase activities of Penicillium simplicissimum H5 during solid-state fermentation with rice straw were studied. Degradation of lignocellulose was also followed. Results showed that all supplemental carbon sources inhibited the laccase activity in different degrees, while suitable concentrations of supplemental nitrogen sources remarkably enhanced the laccase activity. The enhancement of activity by the ordinary laccase inducers 2, 2¢-azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) and xylidine was not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 39 publications
1
14
0
5
Order By: Relevance
“…Members of the molds, as majority of microscopic forms, inhabit lignin-rich environments, and their relative lignin-degrading potential is worth of being studied. It was shown that some of them, such as Aspergillus fumigatus, A. japonicus, A. niger, and A. terreus, Penicillium simplicissimum, were capable of degrading both aromatic and carbohydrate components of water-soluble lignocarbohydrate complexes (LCC) or Kraft lignin (Milstein et al 1984;Zeng et al 2006). Although the function of mold species was noticed, few studies have so far described mold species occurring biodegradation of alkali lignin.…”
Section: Introductionmentioning
confidence: 99%
“…Members of the molds, as majority of microscopic forms, inhabit lignin-rich environments, and their relative lignin-degrading potential is worth of being studied. It was shown that some of them, such as Aspergillus fumigatus, A. japonicus, A. niger, and A. terreus, Penicillium simplicissimum, were capable of degrading both aromatic and carbohydrate components of water-soluble lignocarbohydrate complexes (LCC) or Kraft lignin (Milstein et al 1984;Zeng et al 2006). Although the function of mold species was noticed, few studies have so far described mold species occurring biodegradation of alkali lignin.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that lignin is oxidised and degraded by a ligninase system (Lechner and Papinuti, 2006;Zeng et al, 2006;Elisashvili et al, 2008;Rodrigues et al, 2008) composed by lignin Modification of wheat straw lignin by solid state fermentation with white-rot fungi 24 peroxidase (LiP), manganese peroxidase (MnP) and laccase. In addition, cellulases, hemicellulases and esterases are also considered to be extremely important in the degradation process of lignocellulosic biomass (Ghatora et al, 2006;Tabka et al, 2006;Panagiotou et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Aunque está reportado que Aspergillus y Penicilllium spp son eficaces en la degradación de la lignina (13,22), no se ha descrito su capacidad en la producción de aromáticos a partir de pajas agrícolas ya que los estudios se han enfocado principalmente en basidiomicetos y en la transformación de aromáticos intermediarios. Por ejemplo con Trametes versicolor a partir de ácido ferúlico se generó alcohol veratrílico y veratrilaldehido (23), mientras que con Pycnoporus cinnabarinus se liberó vainillina con un rendimiento de 0,064 mg mL -1 en 7 días (9).…”
Section: Discussionunclassified